THE ROLE OF BIOMATERIALS IN CRANIOFACIAL BONE REGENERATION: AN OVERVIEW (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The regeneration of Craniofascial Bones is a complex and multifaceted process, the role of biomaterials in this process is extremely important. This process is mainly aimed at eliminating the problems caused by damage or loss of bone tissue, and aims to restore the natural structure and function of bones in the craniofacial area. Biomaterials, in turn, serve as a key tool in creating a tissue environment in this process, providing favorable conditions for cell growth and differentiation, as well as promoting the formation of new bone tissue.